Health-related quality of life after Rituximab treatment of patients with antineutrophil cytoplasmic antibody-associated vasculitis - Iva Parvova; Tzvetomir Delyiski; Parvoleta Peteva; Valentina Petkova; Irfan Irfan; Emanuil Yordanov; Emil Hristov (Pensoft Publishers, 2024)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) are severe, socially significant diseases that require a clear understanding of the relationship between the current health status and quality of life of patients. On the one hand, in the scientific literature, there is not enough data to assess the quality of life for the different therapeutic regimens, and no specific tools have been developed to assess functional indicators and health status. On the other hand, with the exception of Rituximab treatment, the available immunosuppressive regimens do not lead to a good clinical response in patients with AAV. The aim of the study is to measure health-related quality of life in a Bulgarian population of patients with systemic vasculitis associated with ANCA undergoing biological treatment with Rituximab by using the generic instrument SF-36 version 2. We conducted a retrospective-prospective, non-interventional, controlled study in two periods in two centers in Bulgaria. Treatment with Rituximab leads to qualitative and quantitative improvement in all components of physical health, including mental and social components. After treatment, all measured parameters were within the normal range for the general population.